Food sources of energy and macronutrient intakes among infants from 6 to 12 months of age : the growing up in Singapore towards healthy outcomes (GUSTO) study - Lim, Shan-Xuan (2018)
Adequate nutrition during complementary feeding is important for the growth, development and well-being of children. We aim to examine the energy and macronutrient intake composition and their main food sources in a mother–offspring cohort study in Singapore. The diets of infants were assessed by 24 h dietary recalls or food diaries collected from mothers when their offspring were 6 (n = 760), 9 (n = 893) and 12 (n = 907) months of age. Food sources of energy and macronutrients were determined using the population proportion methodology. Energy intakes per day (kcal; mean (standard deviation, SD)) of these infants were 640 (158) at 6 months, 675 (173) at 9 months, and 761 (208) at 12 months. Infant formula, breastmilk and infant cereals were the top three food sources of energy and macronutrient intakes in infants through the period 6 to 12 months. Other main energy and carbohydrate sources at 9 and 12 months of age were rice porridge, infant biscuits and fresh fruits, while fish, red meat and eggs were the other main protein and total fat sources. Breast-fed and mixed-fed infants had a more varied diet as compared to formula-fed infants. Formula-fed infants had consistently higher protein and lower total fat consumption compared to those who were breastfed. An understanding of these main food sources during complementary feeding can inform local dietary recommendations and policies.